2016
DOI: 10.3892/mmr.2016.5323
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 inhibits high glucose-induced apoptosis and ROS production in human peritoneal mesothelial cells via the MAPK/P38 pathway

Abstract: The regulation of cell proliferation, differentiation and immunomodulation are affected by 1,25(OH)2D3. However, its function during apoptosis and oxidative stress in human peritoneal mesothelial cells (HPMCs) remains unknown. The aim of the present study was to investigate whether the regulation of apoptosis and oxidative stress have therapeutic relevance in peritoneal dialysis (PD) therapy. The present study investigated the effects of 1,25(OH)2D3 on high glucose (HG)-induced apoptosis and reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Tumour cells with higher ROS levels are more likely to be killed than normal cells with lower ROS levels, as elevated levels of ROS can activate multiple signalling pathways that induce apoptosis such as mitogen-activated protein kinase (MAPK), signal transducer and activator of transcription 3 (STAT3), and nuclear factor-kappa B (NF-jB) signalling pathways [7]. Accordingly, targeting relevant signalling pathways, especially ROS-related pathways, may have potential for lung cancer treatment [8]. Some quinolizidine alkaloids have been reported to exert pro-oxidant actions, which may be an important mechanism for their anticancer and apoptosisinducing properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells with higher ROS levels are more likely to be killed than normal cells with lower ROS levels, as elevated levels of ROS can activate multiple signalling pathways that induce apoptosis such as mitogen-activated protein kinase (MAPK), signal transducer and activator of transcription 3 (STAT3), and nuclear factor-kappa B (NF-jB) signalling pathways [7]. Accordingly, targeting relevant signalling pathways, especially ROS-related pathways, may have potential for lung cancer treatment [8]. Some quinolizidine alkaloids have been reported to exert pro-oxidant actions, which may be an important mechanism for their anticancer and apoptosisinducing properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal dialysis (PD) is a primary treatment of end-stage renal disease (ESRD). High glucose (HG) damages the structure and function of the peritoneal membrane, which leads to peritoneal fibrosis and ultrafiltration failure via inflammation, apoptosis, oxidative stress and epithelial-mesenchymal transition (EMT) (1)(2)(3). Recent studies have also revealed that HG regulates autophagy in certain diseases (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA-15a-5p suppressed PMC EMT (76) and microRNA-21 promoted PMC EMT (77). VDR, PPARγ and PPARβ/δ are also involved in the regulation of PMC activity and homeostasis during peritoneal dialysis (41)(42)(43)(44)(45)(46)(47). As RXRα is a dimerization partner for VDR and PPAR, the role of RXRα in PMC homeostasis during PD was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…RXRα can form heterodimers with other nuclear receptors, including peroxisome proliferator activated receptor (PPAR), vitamin D receptor (VDR) and thyroid hormone receptors, resulting in the involvement of RXRα in multiple signaling pathways (35)(36)(37)(38)(39)(40). Previous studies have shown that vitamin D/VDR can inhibit peritoneal fibrosis and functional deterioration induced by chlorhexidine gluconate by inhibiting PMC EMT (41)(42)(43). Telmisartan inhibits peritoneal fibrosis through PPAR-γ activation (44).…”
Section: Effect Of Astragaloside IV and The Role Of Nuclear Receptor mentioning
confidence: 99%